2022
DOI: 10.3390/ijerph19169984
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Prisoners with Mental Health Disorders in Italy: Lights and Shadows after the Abolition of Judicial Psychiatric Hospitals

Abstract: In Italy, a person suffering from a mental disorder who commits a crime will be given a custodial security order and serve the period of admission at a Residenza per la esecuzione delle misure di sicurezza (REMS) (Residence for the Execution of Security Measures, hereinafter “REMS”). These institutions have been established recently and though equipped with the necessary safety measures, the focus is on psychiatric therapy. Despite being present on a national scale, access is very limited in terms of capacity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Sexual abuse can be broadly defined as including violence against sexual organs, including the introduction of foreign bodies into the vagina or the rectum, rape, and other forced sexual acts, and mental sexual violence, such as forced nudity, sexual humiliation, sexual threats, and forced witnessing of sexual abuse. The prevalence of sexual abuse is high among victims of prison maltreatment [24][25][26][27][28][29][30][31]. Neal et al showed that various factors make it difficult to carry out fact-finding missions.…”
Section: Sexual Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Sexual abuse can be broadly defined as including violence against sexual organs, including the introduction of foreign bodies into the vagina or the rectum, rape, and other forced sexual acts, and mental sexual violence, such as forced nudity, sexual humiliation, sexual threats, and forced witnessing of sexual abuse. The prevalence of sexual abuse is high among victims of prison maltreatment [24][25][26][27][28][29][30][31]. Neal et al showed that various factors make it difficult to carry out fact-finding missions.…”
Section: Sexual Abusementioning
confidence: 99%
“…There are some differences between the forms of sexual torture applied to men and women. Rape in men's prisons was first recognized as a crime by the U.S. Supreme Court in Farmer v. Brennan (1994) [24], which unanimously ruled that the Eighth Amendment's prohibition of cruel and unusual punishment has been violated in cases where prison guards acted with "deliberate indifference" and "ignored a substantial risk of serious harm" to the inmate, noting that sexual abuse "is not part of the punishment that criminals pay for their crimes against society".…”
Section: Sexual Abusementioning
confidence: 99%
“…The conversion to a model of care, based on residential facilities in a community equipped only with clinical personnel (Residence for the Execution of Security Measures, hereinafter "REMS"), is indicated, except for individuals who no longer pose a threat to society, who must be discharged and assisted by the local Mental Health Department. 4 At the same time, the safety measure tool itself was redefined, limiting the possible application time for mentally ill offenders. The transition from the OPG system to the REMS system posed considerable difficulties.…”
mentioning
confidence: 99%